Religiosity and Socio-Ecological Spirituality of Indonesian Community According to Y. B. Mangunwijaya - C. B. Mulyatno (GoAcademica Research & Publishing, 2020)
This study aims to explore the thoughts of Y.B. Mangunwijaya on religiosity and socio-ecological spirituality. By using descriptive-inventive methods and character studies, this research focuses on exploring the ideas of Y.B. Mangunwijaya about religiosity and socio-ecological spirituality rooted in the context of Indonesian society. This study finds an important idea that religiosity is the thrill of every individual in living together in the midst of this universe. Meanwhile, spirituality is the driving force in each individual to work together in developing the quality of life in the midst of a sustainable nature. Religiosity and spirituality are at the core of the experience of religious life. Various groups and local communities of the pluralistic Indonesian society have inherited religiosity and spirituality which includes self-awareness as part of nature sensitivity to various natural problems, competence or skills to maintain the environment and social responsibility to cooperate in developing environmental conservation movements. These four things need to be developed as a point for parties to build unity and cooperation among community members. This idea is a contribution and inspiration to develop the ecoliteracy movement in the community and in the family.